Comparison of sustainability and circularity indicators: downstream vs. upstream supply chain strategies - Marah Almelhem; László Buics; Edit Süle (Discover Sustainability)
Abstract In the quest for sustainable and circular practices within supply chains, both downstream and upstream strategies play pivotal roles. This structured literature review aims to compare the indicators of sustainability and circularity between downstream and upstream supply chain strategies, evaluating their impact through practical cases and empirical studies. The downstream strategies, which focus on waste management, customer engagement, and reverse network planning, are explored alongside upstream strategies such as sourcing environmentally friendly raw materials and integrating design for circularity principles. This paper assesses the efficacy of these strategies through a comprehensive review of scholarly articles, reports, and case studies in achieving sustainability and circularity goals. The literature review reveals that downstream strategies often face challenges related to felxibility and operational efficiency while crucial for managing end-of-life products and optimizing resource utilization. Conversely, upstream strategies, emphasizing eco-friendly sourcing and circular design principles which demonstrate significant potential for long term sustainability and circularity. Practical cases illustrate how upstream interventions can lead to reduced environmental impact, enhanced resource efficiency, and increased product longevity across various industries. Furthermore, the review highlights the interconnectedness of downstream and upstream strategies within the broader supply chain ecosystem. Synergistic approaches that integrate both strategies demonstrate the highest potential for driving transformative change towards sustainable and circular supply chains. Ultimately, this review underscores the importance of integrated approaches that leverage both downstream and upstream strategies to achieve lasting environmental and economic benefits to provides insights for policymakers and researchers seeking to prioritize interventions that maximize sustainability and circularity across the supply chain.